From Moo to Microbes: Pathways for precision fermentation in recombinant protein production - Hanno Kossmann; Özlem Özmutlu Karslioglu; Peter Breunig (Journal of Agriculture and Food Research)
Meeting global protein demands amid climate change, land scarcity, and a projected population of nearly 10 billion by 2050 requires innovative, sustainable approaches. Traditional dairy and beef sectors contribute significantly to greenhouse gas emissions - dairy alone may emit up to 72 kg CO2 eq per kilogram of milk protein. Precision fermentation (PF) has emerged as an alternative that harnesses genetically engineered microbes (e.g., Trichoderma reesei, yeasts) to produce animal-equivalent proteins, offering potential reductions in resource use and environmental impacts compared to livestock systems.This paper synthesizes existing life cycle assessments (LCAs), technical process data, and national agricultural statistics to compare PF-derived proteins - focusing on β-lactoglobulin (β‐LG) -to conventional dairy in Germany. Four scenarios are modeled: (1) reallocating the nation's entire sugar production, (2) using only surplus sugar above Planetary Health Diet recommendations, (3) repurposing maize acreage, and (4) extracting sugar from grasslands. Feedstock requirements (sugar, ammonia, minerals) and energy inputs (electricity for fermentation) were combined to estimate per-kilogram land use for PF proteins under each scenario. Results were then benchmarked against dairy-based β‐LG, which has a land footprint of 19–68 m2/kg depending on allocation rules.Findings indicate that high-yield sugar crops (e.g., sugar beet, maize) or surplus sugar streams could feasibly produce substantial volumes of PF protein while limiting new land requirements. Grass-based feedstock is also viable, albeit with higher land footprints. Key challenges include ensuring green ammonia supplies, integrating renewable energy, and navigating socioeconomic trade-offs such as farm employment and nutrient cycling. Nonetheless, PF may complement or reduce reliance on traditional animal agriculture, particularly where grazing land or sugar surpluses can be redirected without compromising food security. Further research on feedstock optimization, techno-economic feasibility, and policy frameworks-such as incentives for “green” inputs-will be vital to accelerating PF's contribution to a more sustainable protein supply.